Harmonizing Climate Risk Management in Agricultural Extension (CRMAE) Curricula Targeting Livestock Systems - Grossi, Amanda; Borthwick, Fiona; Simm, Geoff; Menéndez, Martín Del Valle; Worou, Nadine; Crane, Todd A.; Belay, Berhanu; Hansen, James (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report presents the outcomes of a regional harmonization workshop held in Nairobi in April 2024 to adapt the Climate Risk Management in Agriculture Education (CRMAE) curriculum for livestock systems across Ethiopia, Kenya, and Senegal. Bringing together meteorological agencies, research institutions, universities, regional institutions, and grassroots and development organizations representing and working with pastoralists, the workshop aimed to align climate risk management competencies and learning outcomes with the realities of pastoralist communities. Through participatory exercises, discussions, and diagnostic tools, the workshop identified key knowledge gaps and opportunities for contextualizing training, integrating local and indigenous knowledge, and improving access to climate information services (CIS). Tools like KAZNET, EDACaP, and WENDOU were examined for their potential in bridging CIS with extension services, while challenges such as digital access, trust, and coordination were discussed. The workshop culminated in consensus on a harmonized set of core competencies and next steps for co-developing localized curriculum materials, thereby strengthening climate-resilient extension for pastoralist systems in East and West Africa.